Searching for a Potential Blue Zone in the Nordics: A Study on Differences in Lifestyle and Health in Regions Varying in Longevity in Western Finland - Sarah Åkerman; Dorly Deeg; Erika Boman; Johan Niklasson; Yngve Gustafson; Fredrica Nyqvist (Journal of Aging Research)
To delay social and healthcare utilisation among the ageing population, there is an increasing focus on the role of health-promoting lifestyle adopted at an individual and/or community level. Longevity is generally viewed as the ultimate outcome of health, although a high life expectancy does not necessarily go together with health and/or a health-promoting lifestyle. The potential coherence between longevity, health and lifestyle may vary in different cultural, political, social and economic contexts. This Nordic regional study situated in regions differing in longevity aims to (i) explore differences in adherence to the comprehensive, health-promoting Blue Zone lifestyle principles in four regions in Western Finland (bilingual Ostrobothnia, Swedish-speaking Åland and Finnish-speaking South Ostrobothnia) and (ii) investigate regional differences in health. Thus, the present study aims to examine if adherence to Blue Zone lifestyle principles and good health is highest in the most longevous region. Survey data from the Gerontological Regional Database in 2021–2022 were used. Marginal means were calculated using ANOVA. The results showed that Åland, Finland’s most longevous region, showed the best health and higher environmental agreeableness, while deviated from several Blue Zone lifestyle principles. Swedish-speaking Ostrobothnia showed good health and adherence to the Blue Zone lifestyle. South Ostrobothnia showed the poorest health but as much adherence to the Blue Zone lifestyle as Swedish-speaking Ostrobothnia. Finnish-speaking Ostrobothnia deviated the most from the Blue Zone lifestyle. The findings imply that Nordic longevous regions do not necessarily adhere to the Blue Zone lifestyle. Future research incorporating individual, community and societal factors could further elucidate whether and how longevity, lifestyle and health are interconnected in different ethnolinguistic contexts to further advance the understanding of healthy ageing and improve the implementation of effective health-promoting initiatives.